Anthropocentrism versus Nature in Jule Verne’s The Master of the World - Angel Kushmi (Contemporary Research: An Interdisciplinary Academic Journal, 2026)
This study unfolds the disparaging skirmish amid anthropocentrism—human-centeredness—and the environment in Jules Verne's novel The Master of the World. Relying on the notions of ecocriticism, the study scrutinizes the ecological snags instigated via unimpeded anthropological interference and the destructive impressions of scientific developments on the ecology. This ecological catastrophe is outlined over the sensitive connections amid the character, Robur, and his natural environments. By applying theoretical philosophies of Greg Garrard's ecocriticism, Rob Boddice's bio-culturalism, Cheryl Glotfelty's eco-foundationalism, and Lewis Wolpert's developmentalism, the study delves deep into what way main anthropological insolences enthusiastically drive ecological misuse. The study finds out that persistent anthropological actions unswervingly cause environmental squalor and the desolation of ecology, revealing a profound splintered association amid humankind and the ecology. Finally, the study settles through an imperative moral appeal: individuals must judgementally replicate on their activities, relinquish an antagonistic visualisation to ecosystem, and vigorously initiate to convalesce a pleasant-sounding relation with the ecology.